1998
DOI: 10.1159/000014327
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function and Oxygen Balance in Septic Patients during Continuous Hemofiltration

Abstract: The aim of this work was to study hemodynamic, oximetric and metabolic parameters in septic patients during continuous hemofiltration, in order to determine whether the changes in hemodynamic parameters can influence the oxygen utilization in peripheral tissues. 29 multiple organ failure patients with septic shock were studied during the first 48 h of continuous hemofiltration: 18 were submitted to CAVH and 11 patients were treated with CAVHD to correct ARF and fluid overload. Our data show that RVEF improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Meloni et al (25) have demonstrated that CHDF is useful in septic patients to correct fluid overload and ARF, without affecting hemodynamic stability and oxygen balance. These results raise a possibility that this technique will improve the prognosis of septic patients complicated with ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Meloni et al (25) have demonstrated that CHDF is useful in septic patients to correct fluid overload and ARF, without affecting hemodynamic stability and oxygen balance. These results raise a possibility that this technique will improve the prognosis of septic patients complicated with ARF.…”
Section: Discussionmentioning
confidence: 99%